How widely do wages vary within jobs in the same establishment? - Sunday, Krista; Pfuntner, Jordan (Monthly Labor Review, 2008)
The article discusses wage dispersion in the U.S., and presents a detailed analysis of various studies on the issue. It specifically refers to the U.S. Bureau of Labor Statistics (BLS) studies conducted 20 years ago by looking at how wages varied within occupations, within establishments, in 2004. An examination of BLS wage data suggests that wages vary widely within a particular job in a particular establishment. A comparison of BLS data from 1983 and 2004 suggests that within-job wage dispersion has increased over that period.